Digital institutions made in EU and the paradox of a regulatory anti-normativism (Sociologia del diritto, 2025)
This article explores the phenomenon of European digital regulation by placing it at the centre of a broader process, that of digital institutionalism, in which the use of data, their regulation, and the management and ownership of digital infrastructures produce social, political and legal effects. By questioning the plausibility of this process as unprecedented, this contribution highlights some of its peculiar features in comparison to classical institutionalism. Digital institutionalism emerged with reference to the European Data Strategy, identifying practices and processes triggered by regulatory phenomena that make technology both an institutional driver and a limit to the regulatory capacity of existing institutions. From the perspective of legal sociology, this contribution investigates the positioning of digital institutionalism in the process of European integration, examining how much this implies adherence to models, formal and informal rules, procedures, and practices that stabilize trends within broader social transformations. It essentially questions three issues: a) the plausibility of the hypothesis of digital institutionalism in light of data governance models; b) its assumptions of applicability; and c) the advantages of using this notion to understand the position.
Keywords: digital institutions; data; law; european integration; single market; global market